A polyoxometalate cluster-based single-atom catalyst for NH3 synthesis via an enzymatic mechanism. Issue 11 (16th December 2021) - Talib, Shamraiz Hussain; Yu, Xiaohu; Lu, Zhansheng; Ahmad, Khalil; Yang, Tongtong; Xiao, Hai; Li, Jun
Abstract : The proposed new non-noble-metal Mo1 /PMASAC is potentially more efficient and more selective than the current best Mo/BN and FeN3 /embedded graphene SAC, and the preferred mechanism is an enzymatic pathway. Abstract : NH3 synthesis by the electrochemical N2 reduction reaction (eNRR) under mild conditions has attracted much attention. Here, by means of the first principles calculations, we propose a new strategy using a transition metal single-atom catalyst (SAC) anchored on a phosphomolybdic acid (PMA) cluster as a heterogeneous catalyst for the eNRR. We have systematically studied three reaction mechanisms, i.e., distal, alternating, and enzymatic pathways, respectively, for the eNRR on a Mo1 /PMA SAC via a six-proton and six-electron process, and found that the preferred mechanism is the enzymatic pathway with the smallest overpotential ( η ) of 0.19 V. N2 is first strongly adsorbed on Mo1 /PMA and then dissociated by the subsequent protonation process. In addition, we found that Mo1 /PMA can impede the hydrogen evolution reaction (HER) process and thus promotes the eNRR selectivity. The high catalytic activity of Mo1 /PMA for the eNRR is attributed to the high spin density on Mo, enhanced N2 adsorption, stabilization of the N2 H* species, and the destabilization of the NH2 * species. The present work is further extended to investigate the kinetics of the conversion of N2 to ammonia on Mo1 /PMA via an enzymatic mechanism. Our results expose that the calculated activation energy barrier for the protonation of N2 to form the N2 H4 * species is kinetically and thermodynamically more favorable compared with other elementary steps. These results provide valuable guidance for NH3 synthesis using SACs at ambient temperature with high efficiency and low cost.